Conceptualizing Women's Work: The Cultural Economy of Weaving - Dayo, Helen F. (Review of Women's Studies; Vol 15 No 2 (2005): Review of Women's Studies Volume XV, Number 2 (July-December 2005), 2006)
Three themes are discussed in this paper, which is based on fieldwork conducted from 1998 to 2000 as part of the author's dissertation: 1) the importance and meanings that women placed on hat weaving; 2) the cultural worldview that shaped and informed the women's perception of weaving; and 3) the integration of women into the market through weaving. Women's stories of Luisiana, Laguna present weaving as an economic interest embedded in their social and cultural environment, making weaving both an economic and socio-cultural activity. For the Luisianahin women, weaving is both a source of livelihood and leisure that allows them to deepen both their kinship and community ties. Likewise, this activity is permanently woven in the tapestry of their own lives. Polanyi's economic model of economic processes re-assert its relevance with the continuing pervasiveness of small, home-based economic activities in the Philippine rural upland. However, the model is gender-blind; the paper shows through the example of the women weavers how the gender perspective can be concretely incorporated in the analysis of economic systems as well as demonstrate the functioning of environment as an important resource linking women in an ecological-economic relationship.